PEDAGOGICAL ASSISTANCE IN HIGH SCHOOL STUDENTS’ PROFESSIONAL SELF–DETERMINATION - V. N. Kormakova; E. N. Musaelian; D. I. Ruziyeva (Образование и наука)
Introduction. The study is complex and extremely topical in modern society and social and cultural reality. The problem is challenging because the pedagogical assistance in self-determination in trade occupations gives a great opportunity to achieve a high level in personal development, in modern production, and in society as a whole.The aim of the study is to develop a concept of pedagogical assistance in self-determination of high school students in the field of trade occupations. Methodology and research methods. The solution of the problems and test assumptions have been provided with the help of the following methods: theoretical analysis of philosophical, psychological, sociological and pedagogical works; diagnostics; observation; archival research; taxonomic qualimetric; pilot, ascertaining and educational experiments; methods of mathematical statistics.Results. The research shows a positive change in creativity, reflexivity and values of high school students in experimental groups. In certain conditions the process of self-determination in trade occupations has been successful.Scientific novelty. There has been developed a scientific concept of pedagogical assistance in self-determination of high school students in the field of trade occupations, which includes the structure, functions, laws and principles, factors, pedagogical conditions and a mechanism to ensure the effectiveness of the selfdetermination process; technological and reflexive foundations of this process.Practical significance. The results of the study can be used in secondary general and vocational education, training, retraining and refreshment courses for teachers, graduate students, tutors and is to create preconditions for pedagogical support for self-determination of high school students in the field of trade occupations.